2010
DOI: 10.1159/000315933
|View full text |Cite
|
Sign up to set email alerts
|

Group Therapy for Patients with Mild Cognitive Impairment and Their Significant Others: Results of a Waiting-List Controlled Trial

Abstract: Background: Patients with mild cognitive impairment (MCI) have to deal with an uncertain prognosis and also face a multitude of memory-related problems and psychosocial consequences. A newly developed group programme proved to be feasible, however, it needed confirmation by a controlled study. Aim: This controlled study evaluates this group therapy for MCI patients aimed to help them accept and manage the memory problems and the psychosocial consequences. The programme combines elements from psychoeducation, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 96 publications
3
40
1
Order By: Relevance
“…However, participants should not feel isolated when learning about these deficits, and feedback and support is often required. In line with our findings, previous research has shown that awareness and acceptance were associated with intervention effectiveness (Joosten-Weyn Banningh et al, 2010). In addition, personal adjustment counselling, which addresses medical issues such as cognitive deficits, has been shown to be helpful with respect to employment outcomes in people with MS (Chiu, Chan, Bishop, da Silva Cardoso, & O'Neill, 2013).…”
Section: Increased Reflection and Awarenesssupporting
confidence: 90%
“…However, participants should not feel isolated when learning about these deficits, and feedback and support is often required. In line with our findings, previous research has shown that awareness and acceptance were associated with intervention effectiveness (Joosten-Weyn Banningh et al, 2010). In addition, personal adjustment counselling, which addresses medical issues such as cognitive deficits, has been shown to be helpful with respect to employment outcomes in people with MS (Chiu, Chan, Bishop, da Silva Cardoso, & O'Neill, 2013).…”
Section: Increased Reflection and Awarenesssupporting
confidence: 90%
“…Previous research indicates that it can decrease perceived stigmatization in skin conditions, 57 improve psychological and disease-related outcomes in psoriasis, 58,59 and decrease helplessness, which shows high correlations with disease impact. [60][61][62] In order to target the SI aspect of type D personality, social skills training and evidence-based interventions for social fears, such as cognitive behavioural therapy and/or exposure therapy, may be an additional treatment approach. 63,64 The current study provides a framework of characteristics of patients who are at greater risk to perceive stigmatization, which has been shown to have detrimental psychological consequences in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…65 Little is known about the effectiveness of multidisciplinary care programs or supportive care interventions (e.g., counseling, education, support groups) for patients with MCI or their families because well-designed RCTs are lackingand one RCT that included many patients with dementia was negative (Table). 16 A few, small RCTs found that psychotherapy may modestly increase patients' acceptance of an MCI diagnosis and also provide knowledge, insight, acceptance, and coping skills for significant others, 66,67 but larger RCTs are needed.…”
Section: Counseling On Behaviorsmentioning
confidence: 99%